Perioperative Analgesic and Sedative Effects of Cannabidiol in Cats Undergoing Ovariohysterectomy - Zanelli, Gustavo Ricci; Vieira, Gabriela Brambilo Menegasso; Souza, Rafaela Vitória Marchini; Aguiar, Antonio José de Araújo [UNESP]; Cassu, Renata Navarro [UNESP] (MDPI, 2024)
The aim of this study was to evaluate the perioperative analgesic and sedative effects of oral CBD in cats undergoing ovariohysterectomy. Twenty-two cats were assigned to receive either oral cannabidiol oil (2 mg/kg, CBD group, n = 12) or placebo oil (0.1 mL/kg, Placebo group, n = 10) 60 min before the premedication. The anesthetic protocol included dexmedetomidine/meperidine, propofol, and isoflurane. Intravenous fentanyl was given to control cardiovascular responses to surgical stimulation. Pain was assessed at 0.5, 1, 2, 4, 6 and 8 h post-extubation using the UNESP–Botucatu multidimensional composite pain scale and the Glasgow feline composite-measure pain scale. Sedation scores were assessed at the same timepoints and at 15 min after the premedication. Morphine was administered as rescue analgesia. Higher sedation scores were recorded in the CBD group at 15 min after premedication (p = 0.041). Intraoperatively, more cats required fentanyl in the Placebo group than in CBD group (p = 0.028). The pain scores did not differ between groups, except at 0.5 h post-extubation when lower scores were detected in the CBD group (p = 0.003–0.005). Morphine was required in 100% of the animals in both groups. CBD increased preoperative sedation and decreased intraoperative analgesic requirements, with minimal evidence of postoperative analgesic benefits over the placebo.
Keywords: analgesia; cannabinoids; pain; surgery